Cognitive Map Ability of Elementary School Students In terms of Gender - Faizah Faizah; Rizky Febri Hendrawan (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2018)
The present study aimed to find out the cognitive map ability difference between male and female students in Elementary School X in Malang City. The present study employed quantitative approach with comparative design. The subject of the study was 331 students, they were selected by using purposive sampling technique. The instrument of the study was achievement test. The data were analyzed using chi-square. The result of the study showed no difference in terms of cognitive map between male and female students. This may occur since the male and female students possessed equal opportunity and need to learn their school environment. Although gender did not emerge as a variable determining the difference of Cognitive Map ability, the aspect that still becomes the determiner of the individuals’ cognitive map ability difference is experience, which the present study referred to Grade and Age difference. The higher the grade and the older the age, the better the cognitive map ability the elementary school students possessed. The school counselor can utilize the result of this study as a reference in developing guidance and counseling program for developing cognitive map ability for male and female elementary school students.